2017
DOI: 10.1177/1099636217720214
|View full text |Cite
|
Sign up to set email alerts
|

Failure analysis of glass-reinforced polyester mortar pipes with different cores subjected to combined loading

Abstract: In this paper, the failure of glass-reinforced polyester mortar pipes with different cores subjected to pure and combined loading are analyzed. To enhance the stiffness of fiber-reinforced polyester pipe, filler layer is incorporated in between fiber-reinforced polyester plies. Thus, in this study, new nanocomposite materials are proposed as a core layer in the glass-reinforced polyester mortar pipes. The performance of the pipes in the presence of nanosilica/resin, nanosilica/fiberglass/resin and multi-walled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
0
2
0
1
Order By: Relevance
“…• Otras matrices como el poliéster isostático [21] o vinil éster están también comercialmente disponibles, aunque su uso es menos difundido.…”
Section: Clasificaciónunclassified
“…• Otras matrices como el poliéster isostático [21] o vinil éster están también comercialmente disponibles, aunque su uso es menos difundido.…”
Section: Clasificaciónunclassified
“…and mode-dependent failure criteria (Chang, Puck, etc.) [36][37]. Hashin criterion, one of the modedependent failure criteria, shows an excellent performance in predicting multiple damage modes (fiber breakages or matrix cracks).…”
Section: Failure Criterionmentioning
confidence: 99%
“…Maximum normal stress, Tsai–Wu and Tsai–Hill criteria are employed for the failure analysis. 9 Rafiee studied the failure of filament-wound GRP pipes with experimental and theoretical methods and revealed that netting analysis that is widely used in GRP pipe industries cannot predict hoop and longitudinal strengths appropriately. Consequently, they developed a sequential failure model to account for Last Ply Failure (LPF) in GRP pipes considering sand layer.…”
Section: Introductionmentioning
confidence: 99%